2015
DOI: 10.18488/journal.aefr/2015.5.7/102.7.959.972
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure of Banking Sector in GCC: An Empirical Investigation

Abstract: This work attempts to identify determinants of capital structure in a sample of commercial banks listed on the Gulf Cooperation Council (GCC) stock markets. To achieve this objective, data about were collected from 47 GCC commercial banks for the period between 2001 and 2010. We find that profitability and liquidity affect banks' capital structure decision. The major contribution of this study is that, the majority of the commercial banks' assets in GCC is financed by debts which represents more than 80 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
1
14
0
7
Order By: Relevance
“…The results are in accord with Anarfo (2015), Al-Mutairi and Naser (2015), Papagianni (2013), Gropp and Heider (2010), Rajan and Zingales (1995), and Sheikh and Qureshi (2017). Nevertheless, contradicts Sghaier and Lahdhiri (2015) and Alraheb et al (2019) conclusion.…”
Section: Regression Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The results are in accord with Anarfo (2015), Al-Mutairi and Naser (2015), Papagianni (2013), Gropp and Heider (2010), Rajan and Zingales (1995), and Sheikh and Qureshi (2017). Nevertheless, contradicts Sghaier and Lahdhiri (2015) and Alraheb et al (2019) conclusion.…”
Section: Regression Resultssupporting
confidence: 80%
“…Rajan and Zingales (1995), with respect to the Pecking order theory, argued that because large firms are less subject to asymmetric information in comparison to small firms they are abler to issue equity that is more sensitive to information asymmetry and thus have lower debt. Alraheb et al (2019) and Al-Mutairi and Naser (2015) found a negative link between leverage and size.…”
Section: Theoretical Developmentmentioning
confidence: 96%
“…In the context of banking, some studies revealed a positive association between leverage and growth since the banks are deficient of internal funds to finance its investment prospects, and due to this, banks need an external fund to cover its insufficiency (Al-Mutairi & Naser, 2015). Furthermore, banks that have a better growth have better chances to acquire funds without difficulty due to its reputation and high diversification which can imposed them to alleged lower level of risk.…”
Section: Existing Studies Of Capital Structure Determinantsmentioning
confidence: 99%
“…It can be found in Titman and Wessels (1988); Rajan and Zingales (1995); Bevan and Danbolt (2001); Hall et al (2004); Hasan and Butt (2009); Frank and Goyal (2009); Khrawish and Khraiwesh (2010) To the best of researcher"s knowledge, the research on capital structure specifically conducted for banks is, however, relatively limited compared to the non-financial firms in which there is few significant understandings on how banks practice its capital structure and what is the determinants or factors that might affect the decision on the capital structure made. Some studies related to banks" capital structure can be found in Kuo and Lee (2003); Asarkaya and Ozcan (2007); Kleff and Weber (2008); Amidu (2007); Gropp and Heider (2010); Octavia and Brown (2010); Juca et al 2012; Shahchera (2013); Al-Mutairi and Naser (2015).As such, this study attempts to shed light on the importance of banks" capital structure by reviewing at the previous literature to address the gaps in the capital structure practices. This paper is organized as follows: Section 2 discuss on the general concept of capital structure practices; Section 3 provides an overview on the existing capital structure theories; Section 4 present the critical review on theories related to banking perspectives; Section 5 carried out the empirical studies on determinants of capital structure and, finally, Section 6 concludes the paper and provides suggestions for further exploration.…”
Section: Introductionmentioning
confidence: 95%
“…Sermaye maliyetindeki artış ve mevduatın negatif etki yaptığı görülmüştür. Mutairi ve Naser (2015) tarafından yapılan çalışmada, Körfez ülkelerindeki seçilmiş bankaların sermaye yapılarını belirleyen faktörlerin ortaya konması amaçlanmıştır. Bu amaçla, 2001-2010 yılları arasında 47 ticari bankanın yıllık verileri ele alınmıştır.…”
Section: Literatür Taramasıunclassified